Articles The situation of milk supplied in child day care centers in the year 2003. - ไตรโรจน์, บุบผา; อึ้งชูศักดิ์, จันทนา; บังเกิดสิงห์, วิไลลักษณ์; เชษฐพฤนท์, สุรางค์ (Thai Dental Public Health Journal, 2003)
Since 1995, milk has been a food supplement provided in day care centers to all children of age 3-5 years old. The survey in 2001 shows that 84% of milk supplied to the children was sweet milk. To decrease sugar consumption in children, “no-sugar milk” was a campaign during 20022003. The objectives of this study were to update the situation of milk supplied in child day care centers during the year 2003 and to study the opinion of parents towards no-sugar milk. Methods Data collection was composed of: 1) information from a company, 2) mail-questionnaires which were sent to every local governor who took care of buying milk for the children (the response rate was 56%), 3) the interview of 398 mothers who live in Rajchaburi. Results The macro picture of milk sold between January - June 2003, 73.4% was sweet milk compared to 75.1% in 2001. 2.9% of day care centers supplied sweet milk for the children. 96.7% of children drink milk everyday at home and 74.5 % of them have 1-2 packs per day. Unfortunately that 80.3 % of them had sweet milk. Although 86.5 % of parents agreed that children should have no-sugar milk and most of their children have no problem of drinking no-sugar milk at school, but they could not manage at home. Parents expected that teachers should help them to convince children to drink no-sugar milk. This study was supported by The Thai Health Promotion Foundation and The Dental Health Division, Department of Health.